Design of the HealthyQue Mobile Application for Hospital Registration Based on Android Using the Design Thinking Approach and UML Modeling - Fajar Mahardika; Rizki Ripai; Sony Veri Shandy; Fazar Sidik; Riki Aldi Pari; Kukuh Muhammad (Ilmu Bersama Center, 2025)
The increasing number of patient visits to hospitals each year poses challenges in providing fast and efficient services, especially during the registration process. Conventional registration systems often cause long queues and patient discomfort. This study aims to design the HealthyQue mobile application as a digital solution for hospital registration based on the Android platform. The application development follows the Design Thinking approach through five stages: empathize, define, ideate, prototype, and test, to deeply explore user needs and behaviors. The results of this process are realized in the form of system modeling using Unified Modeling Language (UML), including use case diagrams, activity diagrams, sequence diagrams, and class diagrams to structurally depict the system's workflow and architecture. This application offers features such as online patient registration, doctor schedule checking, and real-time queue notifications. The implementation of HealthyQue is expected to improve hospital administrative efficiency, reduce patient waiting times, and enhance service quality. The design results demonstrate that the Design Thinking approach effectively produces solutions aligned with user needs, while UML modeling supports the system documentation in a technical and systematic manner.